DOZ047.111: Acute kidney injury in esophageal atresia. (24th June 2019) - Massolo, A C; Conforti, A; Landolfo, F; Columbo, C; Monaco, F; Giliberti, P; Valfré, L; Romiti, A; Caoci, S; Dotta, A; Braguglia, A; Bagolan, P
Abstract: Background: Oesophageal atresia (OA) is characterized by a significant morbidity during the neonatal period. Affected infants are exposed to multiple potentially nephrotoxic factors, predisposing them to acute kidney injury (AKI), which is associated with poorer outcomes. Children who survive neonatal AKI are at risk of long-lasting renal complications (including chronic kidney disease and hypertension). Aims: The purpose of this study is to investigate AKI prevalence in infants with OA and identify potential contributing factors. Methods: Retrospective analysis was conducted on clinical records of patients with OA between 2017 and 2018 in a single referral centre. AKI severity was defined according to established international pRIFLE criteria ( R isk of renal dysfunction, kidney I njury, F ailure or L oss of kidney function and E nd-stage renal disease) based on change in serum creatinine and urine output during hospitalization collected 5 days after birth. Risk factors, (including potentially nephrotoxic medications, significant infection, urine output, blood pressure), and outcome data (length of hospitalization, duration of intubation) were recorded. Statistical analysis was performed using Graphpad. Results: Thirty-nine OA cases were identified; 6 were excluded for lack of data and 33 were included in the study group. Eighteen (55%), who developed AKI (pRIFLE category R isk or I njury), were compared with 15 patients (45%) with no AKI. AKI was significantly higher in infants with long-gap OA ( P  = 0.02), significantly associated with vancomycin administration ( P  = 0.03), with the use of three or more antibiotics during hospitalization ( P  = 0.0005), and with postoperative muscle paralysis ( P  = 0.001). Infants with OA and AKI experienced longer mechanical ventilation ( P  = 0.004) and hospital stay ( P  = 0.003). No significant association was found with hypotension, or steroid exposure. Incomplete recording of urine output prevented stratification of AKI based on this parameter. Conclusions: OA, particularly more severe cases, are at risk of AKI. Renal function should be routinely assessed, during hospitalization and follow-up. Focusing on prevention and avoiding prolonged courses of nephrotoxic medications may improve outcome.